Effects of GAC layer on the performance of gravity-driven membrane filtration (GDM) system for rainwater recycling. (January 2018) - Ding, An; Wang, Jinlong; Lin, Dachao; Zeng, Rong; Yu, Shengping; Gan, Zhendong; Ren, Nanqi; Li, Guibai; Liang, Heng
Abstract: Gravity-driven membrane filtration (GDM) is promising for decentralized rainwater recycling, owing to low maintenance and energy consumption. However, the organic removal by GDM process is sometimes undesirable and the quality of the permeate cannot meet the standard of water reuse. To improve this, granular activate carbon (GAC) was added as a particle layer on the membrane surface of GDM system. Additionally, a system with sand addition and a system with no particle addition were trialed as comparisons, to study the combined effects of particle hindering and adsorption on the removal efficacy of organics and the development of permeate flux. Results showed that GDM with a GAC layer improved removal efficiency of organics by 25%, and that GAC enhanced removal of florescent compounds (e.g., aromatic proteins, tryptophan proteins and humics), compared with the other two systems. Additionally, the permeate flux in three systems stabilized after Day 25, and kept stable until the end of the operation. However, the presence of GAC layer decreased the level of stable flux (3.2 L/m 2 h) compared with the control system (4.5 L/m 2 h). The factors responsible for the lower flux and severe membrane fouling in GAC layer assisted system were the combined effects of particle and adsorption which led to a denser bio-fouling layer with higher amount of biomass and extracellular polymeric substances contents (proteins and polysaccharides). Resistance distribution analyses revealed that GAC layer mainly increased hydraulically reversible resistance (occupied 93%) of the total resistance, indicating that the flux could be recovered easily by simple physical cleaning. Highlights: Effect of GAC layer on the rainwater treatment in GDM system was evaluated. GAC layer on membrane improved organics (florescent proteins and humics) removal. The presence of a GAC layer decreased the level of the stable flux. GAC decreased the porosity and increased biomass and EPS of the fouling layer.